The biocompatibility of a new endodontic paste used in dental trauma - Adriana de Jesus Soares; Maíra do Prado; Mariana Amade Brazão; Brenda Paula Figueiredo de Almeida Gomes; Alexandre Augusto Zaia
Abstract Objective This study investigated the short-term subcutaneous tissue reaction of a new endodontic paste, based on the association among calcium hydroxide [Ca(OH)2], 2% chlorhexidine gel (CHX) and zinc oxide (ZnO) in comparison with a control paste, and the individual substances alone. Material and method Twenty-four male wistar rats were used. Polyethylene tubes containing the materials were implanted into the dorsal connective tissue of rats. Empty implanted tubes served as controls. The materials used were: Ca(OH)2+CHX+ZnO paste in two different proportions (2:1:2) and (2:1:3), a control paste, Ca(OH)2+CHX (2:1), and the substances alone. After time intervals of 2, 3, 7 and 15 days, the animals were euthanized and the specimens prepared for histological processing. Data were evaluated qualitatively according to the levels of tissue repair and the degree of inflammation. Result On the second day all the materials were observed to cause a severe inflammatory response. On the third day, the pastes Ca(OH)2+CHX+ZnO (2:1:2) and (2:1:3) showed reduction in degree of inflammation. On seventh day the tissue was already more organized with presence of collagen fibers in all materials. After 15 days it was found that compound Ca(OH)2+CHX+ZnO (2:1:2) showed areas with no inflammatory infiltrate. Conclusion The experimental pastes, Ca(OH)2+CHX+ZnO in two different proportions (2:1:2) and (2:1:3), showed favorable results with respect to biocompatibility, when evaluated for a short-term.